The Effect of Price on Consumer Buying Interest Asik Creative Gresik East Java - Susanto, Jonathan Ary; Suwaidi, Rahman Amrullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of price on consumer buying interest at Asik Creative in Gresik, East Java. This research was conducted quantitatively. The independent variable is price, and the dependent variable is consumer buying interest. The data collected in this study were collected through the distribution of questionnaires. Consumers who have used the services of Asik Creative are the subject of this study. The number of samples collected was 40 individual consumers who had experienced the experience of communicating with Asik Creative. The data analysis used is quantitative analysis in the first order, each indicator is tested for validity and reliability first and then tested for influence. The study resulted in a statement that price has a significant positive effect on consumer buying interest in Asik Creative. Based on the results of the analysis and discussion, it can be concluded that price has a positive and significant influence on consumer buying interest, which is indicated by a p-value that is smaller than the significant level of 5%.